Digital Learning Training for Islamic Religious Education Students: A Participatory Action Research at STAI Ibnurusyd - Damayanti Romadona; Farouk Fakhruddin; Eka Satari; Maria Ofy Liasari; Ahmad Syarifuddin Zuhri (Amalee: Indonesian Journal of Community Research and Engagement, 2026)
This community service program aimed to improve the digital competence of Islamic Religious Education (PAI) students at STAI Ibnurusyd, who served as the main participants and partners, through digital-based learning training to support Indonesia’s National Digital Education Transformation policy. The program was conducted at STAI Ibnurusyd, involving 30 PAI students, using a Participatory Action Research (PAR) approach comprising planning, action, observation, and reflection stages. Data were collected through pre–post questionnaires using a Likert scale to measure six indicators: understanding digital learning concepts, ability to use digital platforms, creativity in media design, digital literacy, collaborative attitudes, and innovation in microteaching practice, supported by observation and interview data. The results showed an average increase of 50% in participants’ scores across the six indicators, moving from the “moderate” to the “high” competence category. Students demonstrated improved ability to design interactive learning media using applications such as Google Classroom, Canva Edu, and Quizizz. The main outputs of this program include a digital learning training module, examples of interactive learning media products, and a practical implementation model that can be replicated in similar institutions. To support sustainability, a digital learning community was established among students to ensure continued practice and mentoring after the program. This program contributes to strengthening prospective PAI teachers' readiness to become professional educators with digital competence and supports innovation in Islamic higher education.